The Twenty-First Century Challenges To Sexuality and Religion - Turner, Yolanda (Journal of religion and health, 2014)
Clergy and religious leaders are facing a wide variety of sexual needs and concerns within their faith communities. Conflicts over sexual issues are growing across the entire spectrum of religious denominations, and clerics remain ill prepared to deal with them. As religious communities work to remain influential in public policy debates, clergy and the institutions that train them need to be properly prepared for twenty-first century challenges that impact sexuality and religion. Clergy are often the first point of contact for sexual problems and concerns of their faith community memberscomplex issues centered on morals, spirituality, and ethics. Yet, there still exists a significant lack of sexual curricula in the programs that are educating our future religious leaders. The resulting paucity of knowledge leaves these leaders unprepared to address the needs and concerns of their congregants. However, with accurate, relevant human sexuality curricula integrated into theological formation programs, future leaders will be equipped to competently serve their constituencies. This paper provides a rationale for the need for such training, an overview of the faith- and theology-based history of a pilot training project, and a description of how the Christian faith and the social sciences intersect in a training pilot project's impetus and process.